Runoff Prediction Using an Aggregation Hydrology Model on Seulimum River Sub Watershed, Aceh Province, Indonesia - Susi Chairani; T. Ferijal; Ulva Heryanty (Aceh International Journal of Science and Technology, 2014)
The objective of the present study was to predict the runoff in Seulimeum River sub watershed by utilizing an aggregation hydrology model. The method in this research consisted of field observation, collecting data and map, testing model, and analyzing data. Some parameters were used as the inputs on the model, such as: maximum storage, actual groundwater storage, soil moisture, and the constant of soil moisture k(t). The aggregation hydrology model was tested using 3 (three) statistical parameters, such as; determination coefficient (R2), biased percentage (PBIAS), and Nash-Sutcliffe coefficient (ENS). The result showed that the minimum runoff occured in 1998 was 70.22 mm and the maximum runoff occurred in 1987 was 759.12 mm. The model testing showed that the aggregation hydrology model had a good performance in predicting the discharge of Krueng Seulimemum Sub Watershed; the R2, P biased, and ENS resulted 0.92, -5.21%, and 0.90, respectively